2011
DOI: 10.1142/s0218127411030210
|View full text |Cite
|
Sign up to set email alerts
|

Vibration of Circular Bladed Disk With Imperfections

Abstract: The steady state response of a model of circular bladed disk with imperfection is investigated. Disk imperfection results from additional two groups of damping heads fixed on opposite ends of one diameter. These damping heads are introduced into the computing model as additional point mass, damping and stiffness. Such type of imperfection causes the bifurcation of double eigenfrequencies into pairs of close eigenfrequencies. The effect of imperfection is examined both numerically on three-dimensional nonrotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…This experimental work is closely linked to the project dealing with aeroelastic couplings and dynamic behaviour of rotational periodic bodies [5,6]. Vimmr et al [5] carried out a numerical study which uses a simplified model of blade cascade (3 airfoils) which perform harmonic motion and with individual inter-blade phase angle.…”
Section: Introductionmentioning
confidence: 99%
“…This experimental work is closely linked to the project dealing with aeroelastic couplings and dynamic behaviour of rotational periodic bodies [5,6]. Vimmr et al [5] carried out a numerical study which uses a simplified model of blade cascade (3 airfoils) which perform harmonic motion and with individual inter-blade phase angle.…”
Section: Introductionmentioning
confidence: 99%
“…[4] revealed that the flow is mainly affected by the changing wing angle and the effect of displacement is rather small. This experimental work is closely linked to the project dealing with aeroelastic couplings and dynamic behaviour of rotational periodic bodies [5,6]. Vimmr et al [5] carried out a numerical study which uses a simplified model of blade cascade (3 airfoils) which perform harmonic motion and with individual inter-blade phase angle.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to determine the aerodynamic damping coefficients caused by the aerodynamic forces acting on the flat plates. Půst et al [6] has described analytically the dynamic properties of the five-blade-cascade excited by the running harmonic external forces and aerodynamic selfexcited forces were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Zinkovskii and Kruglii [16] used FEM to investigate the effect of possible identity violations of contact interaction between shrouds on the static stress state characteristics of blades. Pust and Pesek [17] investigated the response of circular bladed disk with shrouds. They found that the high of resonance peaks is strongly affected by the nonproportional distribution of damping.…”
Section: Introductionmentioning
confidence: 99%